2014
DOI: 10.4041/kjod.2014.44.6.281
|View full text |Cite
|
Sign up to set email alerts
|

Three-dimensional assessment of upper lip positional changes according to simulated maxillary anterior tooth movements by white light scanning

Abstract: ObjectiveEsthetic improvements during orthodontic treatment are achieved by changes in positions of the lips and surrounding soft tissues. Facial soft-tissue movement has already been two-dimensionally evaluated by cephalometry. In this study, we aimed to three-dimensionally assess positional changes of the adult upper lip according to simulated maxillary anterior tooth movements by white light scanning.MethodsWe measured changes in three-dimensional coordinates of labial landmarks in relation to maxillary inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
13
0
6

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(21 citation statements)
references
References 18 publications
(17 reference statements)
2
13
0
6
Order By: Relevance
“…Furthermore, both the LC and ZC exhibited positive and negative errors in the inner face generated during the process of combining the digital impressions of the crown. These findings support those of previously published studies on this topic 29303132333435363738394041. The quantitative evaluation of the marginal adaptation is not yet standardized and can be misleading 42.…”
Section: Discussionsupporting
confidence: 84%
“…Furthermore, both the LC and ZC exhibited positive and negative errors in the inner face generated during the process of combining the digital impressions of the crown. These findings support those of previously published studies on this topic 29303132333435363738394041. The quantitative evaluation of the marginal adaptation is not yet standardized and can be misleading 42.…”
Section: Discussionsupporting
confidence: 84%
“…While direct anthropometry has always been accepted as the gold standard in facial analysis because of its simplicity and low cost, the need for long clinical sessions and well-trained examiners has been a hindrance [30][31][32] . Stereophotogrammetry presents a safe, non-invasive technique free of ionizing radiation in longitudinal studies 33 .…”
Section: Discussionmentioning
confidence: 99%
“…1 Among the facial soft tissue changes resulting from orthodontic treatment, there is particular interest in changes in the position and contour of the lips, and various methods of predicting posttreatment soft tissue changes have been reported to establish a diagnosis and treatment plan. [2][3][4][5] Choi et al 2 reported that in adult female patients with Class II Division 1 malocclusion, the ratios of movement between labrale superioris (Ls) and labrale inferioris (Li) to the extent of anterior teeth retraction are 1:0.45 and 1:2.08, respectively, and that the amount of posterior movement of Ls is correlated with posterior movement of the maxillary incisal edge.…”
Section: Introductionmentioning
confidence: 99%